Possible Factors Affecting Pre-School Children's Irregular Posture Formation - Laura Daniusevičiūtė-Brazaitė; Rūta Beistarytė (Lithuanian Sports University, 2020)
Background. A review of the health and physical activity of children and teenagers in Lithuania over the last twenty years has shown that many aspects of pupil physical capacity have deteriorated between 1992 and 2012 (Venckunas, Emeljanovas, Mieziene, & Volbekiene, 2017). Also research has shown that musculoskeletal disorders were most commonly found in children aged 4 to 6 years (Daniusevičiutė-Brazaitė & Grėbliauskienė, 2019). Therefore, if these negative trends continue, the growing health problems will pose a greater threat to human well-being and become a serious financial burden for the state and society. Currently technologies are an integral part of everyday life, so the need for interactive games or animated programs cannot be doubted. Research (Lobel, Engels, Stone, Burk, & Granic, 2017) has shown that the use of play-based intervention for children significantly improves fine and visual motor performance. Hence, it is important to identify the possible factors affecting pre-school children's irregular posture formation. Methods. The study included 377 preschool children from 4 to 6 years old. Three evaluations were performed in the study: posture (using W. K. Hoeger posture assessment methodology), abdominal and back muscle endurance, and balance (Arcinavičius,, Kesminas, & Milčarek, 2004). Results. Assessing the results of the shoulder position of 5-year-old children, results showed that only 16% had good shoulder posture, satisfactory - 74%, bad - 10%. Age was found to have no effect on posture assessment results. According to the study, balance, back, and abdominal functional capacity were better in 6-year-old children. Conclusion. After analyzing 4-year old children group torso, abdomen, lower spine and legs, we can see that a higher percentage of children had a satisfactory posture in the aforementioned body parts. According to the posture results, the most abnormal part of the body was the abdomen. The study data showed that 6-year-old subjects' balance, lower spine and abdominal performance were better compared to other age groups. Keywords: preschool child, physical activity, posture.